Engenharia de tráfego como ferramenta de mobilidade: concepções iniciais à melhoria da locomoção na Avenida Independência em Pau dos Ferros/RN - Pereira, Francisco Carlos (Universidade Federal Rural do Semi-Árido, 2018)
The growth of Brazilian cities without use planning and occupation of urban land has been marked in the last three decades as a result of migrations with the rural exodus, and in them, the search for housing spontaneously. The peripheralization of the centers becomes accentuated, giving rise to the installation of a series of social and urban impasses, mainly in relation to the population's demand for equipments of education, health and leisure. At this point, issues related to the promotion of mobility are placed, to the detriment of the greater request of travel and use of motorized transport, in order to search for quick and efficient access to the demands placed. Chaotic traffic, imminent risks in locomotion, lack of accessibility, besides the deficient traffic infrastructure, appear the lack of efficient actions to improve mobility, and indicate the need for measures to mitigate the neglect seen. Traffic Engineering emerges as a response to these concerns, bringing practical and theoretical tools to the uncontrol of the traffic that already establishes itself as one of the main demands of the urbe. The city of Pau dos Ferros, located in the western mesoregion of the Brazilian state, Rio Grande do Norte, exemplifies the configuration in screen, being the section of highway BR 405 one of the most critical points regarding the reality of the local transportation system. In this perspective, the present research aims to propose measures of readjustment in the transit of the said highway, in the stretch in which the Independência Avenue is located, propitiating the efficiency in the transference by the region with a view to the safety of the pedestrians and drivers. In fact, the mapping of the conflict zones of the studied section is carried out, in order to understand the main demands of the traffic infrastructure and characteristics of the local road system, in the idealization of a preliminary project as an action plan to improve the conditions seen.
Keywords: Mobilidade urbana; Infraestrutura de tráfego; Sistema viário; Planejamento; ENGENHARIAS::ENGENHARIA CIVIL